Thermodynamic integration network approach to ion transport through protein channels: Perspectives and limits. Issue 30 (11th October 2018) - Na, Sehee; Steinbrecher, Thomas; Koslowski, Thorsten
Abstract : We present a molecular dynamics simulation study of alkali metal cation transport through the double‐helical and the head‐to‐head conformers of the gramicidin ion channel. Our approach is based on a thermodynamic integration network, which consists of a sequence of transport reactions, absolute free energies of solvation and cycles of alchemical transmutations of the ions. In this manner, we can reliably estimate free energies and their statistical errors via a least‐squares method without imposing external forces on the system. Within the double helical channel, we find a free energy surface typical for hopping transport between isoenergetic sites of ion localization, separated by comparatively large activation barriers. For fast transport through the head‐to‐head conformation, the thermodynamic network scheme starts to break down. © 2018 Wiley Periodicals, Inc. Abstract : Ion migration in the gramicidin protein channel is simulated using a thermodynamic integration network, which consists of transport reactions, absolute free energies of solvation and alchemical transmutations of ions. For a double helical channel, we find a free energy surface typical for hopping transport between isoenergetic sites of ion localization, whereas the scheme starts to break down for fast transport through a head‐to‐head conformation.